Influence of the addition of flaxseed and yam mucilage on the technological characteristics of muffins for phenylketonurics (Research, Society and Development, 2020)
Gluten-free and lactose-free cakes are present in the food market, but they may contain ingredients with amino acid phenylalanine, restricting their consumption by patients with phenylketonuria. The objective of this work was to use flaxseed gel (GL) and yam mucilage (MI) to replace albumin, eggs and soy extract of muffins without the addition of sucrose, gluten and lactose. A complete central rotational design 22 (p